2019
DOI: 10.1021/acs.jpcb.9b00072
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Fast Structural Dynamics in pH-Responsive Peptides with Time-Resolved X-ray Scattering

Abstract: Many biomaterials can adapt to changes in the local biological environment (such as pH, temperature, or ionic composition) in order to regulate function or deliver a payload. Such adaptation to environmental perturbation is typically a hierarchical process that begins with a response at a local structural level and then propagates to supramolecular and macromolecular scales. Understanding fast structural dynamics that occur upon perturbation is important for rational design of functional biomaterials. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 36 publications
(85 reference statements)
0
14
0
Order By: Relevance
“…[13][14][15][16][17][18] ). Unfortunately, the number of proteins that undergo specific photochemistry as part of their functional cycle is small, and there is a fundamental need to develop generalized methods that can be used to synchronously excite conformational transitions in any protein molecule and expand the utility of time-resolved structural experiments [19][20][21][22][23][24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18] ). Unfortunately, the number of proteins that undergo specific photochemistry as part of their functional cycle is small, and there is a fundamental need to develop generalized methods that can be used to synchronously excite conformational transitions in any protein molecule and expand the utility of time-resolved structural experiments [19][20][21][22][23][24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…Transient pH-jump IR spectroscopy studies have shown more transient conformational states of PGA with larger PGA systems . A pH-jump TRXSS experiment showed a transient charged intermediate in the longest (200-residue) PGA . Both studies point toward a nucleation-propagation folding mechanism, triggered by a sudden pH decrease.…”
Section: Time-resolved Characterizations For MD Structural Refinementmentioning
confidence: 95%
“…70 A pH-jump TRXSS experiment showed a transient charged intermediate in the longest (200residue) PGA. 51 Both studies point toward a nucleationpropagation folding mechanism, triggered by a sudden pH decrease.…”
Section: Structural Probes Following a Perturbationmentioning
confidence: 99%
See 2 more Smart Citations